2004
DOI: 10.1074/jbc.m400843200
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin Regulates Cytoskeletal Organization through Binding to ZRP-1, a Member of the Lim Family of Proteins

Abstract: Endoglin is a component of the transforming growth factor-␤ receptor complex abundantly expressed at the surface of endothelial cells and plays an important role in cardiovascular development and vascular remodeling. By using the cytoplasmic domain of endoglin as a bait for screening protein interactors, we have identified ZRP-1 (zyxin-related protein 1), a 476-amino acid member that belongs to a family of LIM containing proteins that includes zyxin and lipoma-preferred partner. The endoglin interacting region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 137 publications
(130 citation statements)
references
References 59 publications
10
119
0
1
Order By: Relevance
“…This is consistent with the previous data in endothelial cells where endoglin has been shown to bind directly to zyxin and to sequester zyxin and its binding partners p130cas and CrkII away from focal adhesion complexes (Conley et al, 2004). In addition, endoglin has been shown to interact with zyxin-related protein 1 resulting in a dramatic change in the structure of the actin cytoskeleton and the localization of zyxinrelated protein 1 (Sanz-Rodriguez et al, 2004). Second, in addition to TGF-b1, endoglin can bind, in association with different TGF-b superfamily receptors, to BMP2, BMP7, BMP9, activin A and TGF-b3 (Cheifetz et al, 1992;Barbara et al, 1999;Scharpfenecker et al, 2007), and has been reported to have a functional role in modulating responses to BMP2 (Ishibashi et al, 2010) and BMP7 (Scherner et al, 2007) in periodontal ligament cells and myoblasts, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the previous data in endothelial cells where endoglin has been shown to bind directly to zyxin and to sequester zyxin and its binding partners p130cas and CrkII away from focal adhesion complexes (Conley et al, 2004). In addition, endoglin has been shown to interact with zyxin-related protein 1 resulting in a dramatic change in the structure of the actin cytoskeleton and the localization of zyxinrelated protein 1 (Sanz-Rodriguez et al, 2004). Second, in addition to TGF-b1, endoglin can bind, in association with different TGF-b superfamily receptors, to BMP2, BMP7, BMP9, activin A and TGF-b3 (Cheifetz et al, 1992;Barbara et al, 1999;Scharpfenecker et al, 2007), and has been reported to have a functional role in modulating responses to BMP2 (Ishibashi et al, 2010) and BMP7 (Scherner et al, 2007) in periodontal ligament cells and myoblasts, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, these data led us to postulate that ALK1 could play an important role in the transition of endothelial cells to the maturation phase of angiogenesis through inhibition of proliferation and migration of endothelial cells. It is interesting to remark that similarly to our observations, recent investigations have revealed a novel function for endoglin, the non-signaling member of the TGFb1 receptor family, in which mutations are responsible of HHT1, in modulating actin cytoskeleton organization and cell migration (Conley et al, 2004;Sanz-Rodriguez et al, 2004;Muenzner et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, in cells in which both isoforms are cosynthesized, the presence of L-S heterodimers, in addition to L-L and S-S homodimers, would add a new level of functional complexity to the endoglin molecule. In this respect, it is tempting to speculate that the ability to modulate TGF-b responses, as a result of the interaction of the L and S cytoplasmic domains with TGF-b receptors (Guerrero-Esteo et al, 2002), or the association with cytoskeletal components (Conley et al, 2004;Sanz-Rodriguez et al, 2004) would be different for the distinct endoglin dimers. Endoglin is upregulated in angiogenic endothelial cells, and several studies suggest that it is required for angiogenesis (reviewed in Li et al, 2001;Duff et al, 2003).…”
Section: Discussionmentioning
confidence: 99%